Social risks in the conditions of financial crisis - Sillaste, Galina (Ukrainian Sociological Journal, 2015)
Theoretical basis and scientific approaches to the study of risks are described in the paper. Peculiarities of social risks, their classification criteria, objects and subjects are analyzed. Typology of social risks of financial and economic crises is provided. The 20 most widespread social risks of financial crisis are highlighted. The characteristics of such risks like the risk of neuroticism, the risk of «victim complex», risk of ekonocide, gender risks are provided.